Cardiovascular burden is high in pediatric lung transplant recipients - Memaran, Nima; Onnen, Mareike; Müller, Carsten; Schwerk, Nicolaus; Carlens, Julia; Borchert-Mörlins, Bianca; Bauer, Elena; Blöte, Ricarda; Sugianto, Rizky I.; Zürn, Katharina; Wühl, Elke; Warnecke, Gregor; et al. (Transplantation, 2022)
Export - Background. - Cardiovascular morbidity is common in adults after lung transplantation (LTx) but has not been described for pediatric LTx recipients. Early subclinical cardiovascular damage is reflected by increases in pulse wave velocity (PWV; indicating arteriosclerosis), intima-media thickness (IMT; indicating atherosclerosis), and left ventricular mass index (LVMI; indicating left ventricular hypertrophy). - Methods. - We annually assessed 47 pediatric LTx recipients in a prospective longitudinal study (144 observations, mean 3.1 visits/patient, range of 1-4 visits, mean follow-up 2.2 y). - Results. - At inclusion, increased PWV and IMT were detected in 13% and 30%, respectively, and elevated LVMI was detected in 33%. Higher PWV was associated with male sex, longer time since LTx, higher diastolic blood pressure, and lower glomerular filtration rate. Male sex and lower hemoglobin levels were associated with higher IMT, and the presence of diabetes was associated with higher LVMI. - Conclusions. - Pediatric LTx recipients suffer from a high and sustained burden of subclinical cardiovascular damage. In light of improving long-term outcomes, cardiovascular morbidity needs to be addressed. Our analysis identified classical and nonclassical risk factors to be associated with the measures for cardiovascular damage, which could serve as targets for intervention.